PENINGKATAN HASIL BELAJAR DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN KOOPERATIF STAD - Darma, Darma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this study was to describe the improvement of student learning outcomes in learning Civics with type STAD cooperative approach in 13 fifth grade elementary school Sungai Aur. The approach used in this study is a qualitative and quantitative approach consisting of two cycles, and each cycle of planning, implementation, observation, and reflection. The subjects were students of class V SDN 13 Sungai Aur. Civics learning outcomes using type STAD cooperative approach has increased. In planning an increase from the first cycle is 76.75% (enough) to 96.4% (very good) in the second cycle. On the implementation of aspects of teacher learning that the first cycle of 74.95% (average) to 91.7 (very good) in the second cycle. Then the student aspect of the first cycle, from 73.6% (enough) to 94.4% (very good) in the second cycle. Learning outcomes can be seen in the recapitulation of the second cycle of student learning outcomes is higher when compared with the first cycle is 71.8% (average) and the second cycle is 85.45% (both) seen an increase of about 13.65%. It can be concluded that the type STAD cooperative approach to improve student learning outcomes in the classroom V SD Negeri 13 Sungai Aur. Kata kunci: peningkatan; hasil; belajar; kooperatif; stad.